2023
DOI: 10.3390/su151914181
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Ecological and Reclamation Condition of Abandoned Saline Lands and Their Development for Sustainable Development Goals

Shakhislam Laiskhanov,
Zhassulan Smanov,
Kulyash Kaimuldinova
et al.

Abstract: To provide the population with food, it is very important to re-cultivate “abandoned lands” that have been retired from agricultural use. The conversion of arable land into agricultural abandoned lands in the south of Kazakhstan is, first of all, primarily associated with salinity. For the purposes of sustainable development, there is a need to develop proposals for re-mastering by studying their current state and reviewing world studies on the reclamation of salt-affected soils. Therefore, this study is devot… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Similarly, Rodrigues et al [ 51 ] observed that adding biochar to stressed and unstressed tomato plants significantly improved the photosynthetic and transpiration rates. Additionally, the use of biochar improved the leaf gas exchange and LWRC under salinity and drought stress conditions, indicating that biochar helped the plants retain firm leaves under abiotic stresses [ 17 ]. In this study, the decreased chlorophyll could be due to damage to the thylakoid membranes, as a result of the destructive effect of reactive oxygen species (ROS) on chloroplasts [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, Rodrigues et al [ 51 ] observed that adding biochar to stressed and unstressed tomato plants significantly improved the photosynthetic and transpiration rates. Additionally, the use of biochar improved the leaf gas exchange and LWRC under salinity and drought stress conditions, indicating that biochar helped the plants retain firm leaves under abiotic stresses [ 17 ]. In this study, the decreased chlorophyll could be due to damage to the thylakoid membranes, as a result of the destructive effect of reactive oxygen species (ROS) on chloroplasts [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…The agricultural practices commonly advised for commercial tomato production in greenhouses were utilized, which encompassed soil sterilization, insect management, and fertilizer. The local farmers followed the required application rates of 238 kg potassium, 142 kg phosphorus, and 285 kg nitrogen per acre for fertilizers during the growing seasons [ 17 ]. The greenhouse was the designated location for installing the surface drip irrigation system.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite these problems, active steps have recently been taken to restart agriculture on abandoned and saline lands, including through organic methods for their restoration [53].…”
Section: The Southern Belt Of Irrigated Agriculturementioning
confidence: 99%